Comparing the effectiveness of schema therapy and therapy based on acceptance and commitment in reducing anxiety and despair of women after divorce - Poorshirazi, Kimia; Sharei, Amane; Salahshouri, Azadeh; Shahhouseini, Arezoo; Ilghami Azar, Nazanin (Applied Family Therapy Journal (AFTJ), 2021)
Aim: The purpose of this research was to compare the effectiveness of schema therapy and therapy based on acceptance and commitment ACT in reducing anxiety and despair in women after divorce. Methods: In terms of practical purpose and in terms of quasi-experimental information gathering method, this research was verified with a pre-test, post-test and follow-up phase with the witness group. The statistical population of this study was the divorced women of Tehran, who were screened based on the initial assessment through Beck's anxiety questionnaire (1990) and Beck's frustration (1974), and 30 women with high scores were selected and randomly assigned to three experimental and control groups. Schema therapy test based on the protocol of Yang et al. (2003) and the experimental group of treatment based on acceptance and commitment based on the protocol of Hayes (2006) underwent eight 90-minute sessions and the control group was placed in a waiting state. The data collected from the three stages of pre-test, post-test and follow-up were analyzed using SPSS software and through the variance of repeated measures. Results: The results showed that schema therapy on the score of anxiety (F=6.88, P=0.021) and hopelessness (F=8.00, P=0.001322) and treatment intervention based on acceptance and commitment on the score of anxiety (F=0.00 F = 7, P = 0.022) and hopelessness (F = 7.20, P = 0.020) were effective in women after divorce, and this effect was reported to be stable in the follow-up stage as well (P = 0.05); Also, the follow-up test showed that the therapy based on acceptance and commitment is more effective than schema therapy. Conclusion: Therefore, paying attention to schema therapy and acceptance/commitment in counseling and psychotherapy environments is of particular importance to reduce anxiety and despair in divorced women.